Caffey’s Disease (Infantile Cortical Hyperostosis) - Paria, Pradipprava; Halder, Ramesh Chandra; Ghosh, Sibarjun (Journal of Nepal Paediatric Society, 2016)
Caffey's disease is a rare, self limiting condition of infancy. Most commonly mandible, clavicle and ulna are affected leading to inflammation of periosteum and overlying soft tissue. We here present an 1 year 3 month old girl with features of Caffey's disease. J Nepal Paediatr Soc 2015;35(3):312-313